2017
DOI: 10.1177/1043659617705436
|View full text |Cite
|
Sign up to set email alerts
|

Building Nursing and Midwifery Capacity Through Rwanda’s Human Resources for Health Program

Abstract: Global disparities in the quantity, distribution, and skills of health workers worldwide pose a threat to attainment of the Sustainable Development Goals by 2030 and deepens already existing global health inequities. Rwanda and other low-resource countries face a critical shortage of health professionals, particularly nurses and midwives. This article describes the Human Resources for Health (HRH) Program in Rwanda, a collaboration between the Ministry of Health of Rwanda and a U.S. consortium of academic inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 22 publications
0
25
0
2
Order By: Relevance
“…In Rwanda, there are approximately 300,000 births per year [25]. Because of insufficient midwives, pregnancy surveillance and delivery care are mostly provided by nurses at health centres, with referrals to higher levels of healthcare in case of complications [29]. There are three educational levels for nurses and midwives: A0, with a bachelor’s degree after 4 years of training at university level; A1, with a diploma after completing 3 years at an institute of higher education; and A2, with lower level training within the secondary school system [30].…”
Section: Introductionmentioning
confidence: 99%
“…In Rwanda, there are approximately 300,000 births per year [25]. Because of insufficient midwives, pregnancy surveillance and delivery care are mostly provided by nurses at health centres, with referrals to higher levels of healthcare in case of complications [29]. There are three educational levels for nurses and midwives: A0, with a bachelor’s degree after 4 years of training at university level; A1, with a diploma after completing 3 years at an institute of higher education; and A2, with lower level training within the secondary school system [30].…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted in Rwanda revealed that challenges in the clinical setting included the shortage of clinical supervisors, or turnover and often the absence of clinical supervision in a severely resource-constrained environment. [9] In this study, most participants reported that EP was more user friendly (easy to read and to navigate, easily accessible everywhere) when compared to PBP. This is similar to the findings from Pincombe [24] where students said that EP is simple, organized, and safe while PBP is not easy and not clear.…”
Section: Discussionmentioning
confidence: 71%
“…[8] Notably, neonates accounted for 39% of all deaths among children under five in 2011. [9] As the density of midwives has been found to be positively associated with immunization coverage and maternal, infant, and child survival. [10] It is important to strengthen the education of future midwives so that more competent midwives can help to achieve the Rwandese healthcare objectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The University of Rwanda, School of Nursing and Midwifery started Masters of sciences in Nursing in eight nursing specialities including perioperative nursing. [2] This nursing speciality deals with care of patient before, during and after surgery. The three selected referral hospitals were used to provide clinical experiences.…”
Section: Introductionmentioning
confidence: 99%